Culture of sustainability and marketing orientation of Indian agribusiness in implementing CSR programs: Insights from emerging market - Anup Raj; Andrej I. Kuznecov; Thankom Arun (Journal of Risk and Financial Management, 2020)
The debate regarding the suitability of market orientation or culture of sustainability for corporate social responsibility (CSR) implementation and economic sustainability deserve much more scholarly attention as globalization and competition in emerging markets increases. Using qualitative content analysis of interviews with 28 senior managers of large agribusiness firms in India, this empirical article explores how market orientation or culture of sustainability affects CSR implementation, or vice versa? The findings of the study identify factors such as the nature of a firm's business, sensitivity, commitment towards sustainable development, and pressure on profitability that prompt firms to adopt sustainability dominant, market dominant, and sustainability–market mixed corporate culture. Culture of sustainability dominant firms are likely to implement CSR more smoothly and effectively compared to firms that are driven by market orientation. Moreover, firms committed to substantial and consistent CSR are likely to induce culture of sustainability in firms. Finally, the study offers a framework that provides insights into how CSR program implementation and a culture of sustainability are complementary and could strengthen the economic sustainability of firms in emerging markets.
Keywords: 330; emerging markets; corporate social responsibility; culture of sustainability; market orientation